Learning from a multidisciplinary randomized controlled intervention in retirement village residents. Issue 3 (28th October 2021) - Bloomfield, Katherine; Wu, Zhenqiang; Broad, Joanna B.; Tatton, Annie; Calvert, Cheryl; Hikaka, Joanna; Boyd, Michal; Peri, Kathy; Bramley, Dale; Higgins, Ann‐Marie; Connolly, Martin J.
Abstract: Background: Retirement villages (RVs), also known as continuing care retirement communities, are an increasingly popular housing choice for older adults. The RV population has significant health needs, possibly representing a group with needs in between community‐dwelling older adults and those in long‐term residential care (LTC). Our previous work shows Gerontology Nurse Specialist (GNS)‐facilitated multidisciplinary team (MDT) interventions may reduce hospitalizations from LTC. This study tested whether a similar intervention reduced hospitalizations in RV residents. Methods: Open‐label randomized controlled trial in which 412 older residents of 33 RVs were randomized (1:1) to an MDT intervention or usual care. Setting: RVs across two District Health Boards in Auckland, New Zealand. Residents were eligible if considered high risk of health/functional decline (triggering ≥3 interRAI Clinical Assessment Protocols or needing special consideration identified by GNS). Intervention: GNS‐facilitated MDT intervention, including geriatrician/nurse practitioner and clinical pharmacist, versus usual care. Primary outcome was time from randomization to first acute hospitalization. Secondary outcomes were rate of acute hospitalizations, LTC admission, and mortality. Twelve residents died before randomization; all others ( n = 400: MDT intervention = 199; usual care = 201) were included in intention‐to‐treat analyses. Results: Mean (SD) age was 82.2 (6.9) years, 302 (75.5%) were women, and 378 (94.5%) were European. Over median 1.5 years follow‐up, no difference was found in hazard of acute hospitalization between the MDT intervention (51.8%) and usual care (49.3%) groups (Hazard ratio [HR] = 1.01, 95% CI = 0.77–1.34). No difference was found in the incidence rate of acute hospitalizations between the MDT intervention (0.69 per person‐year) and usual care (0.86 per person‐year) groups (incidence rate ratio = 0.81, 95% CI = 0.59–1.10). Similar results were seen for the proportion of residents with LTC transition (HR = 1.18, 95% CI = 0.65–2.11) and mortality (HR = 0.70, 95% CI = 0.36–1.35). Conclusion: Further studies are needed to assess the effects of other patient‐centered interventions and outcomes with adequate primary care integration.